Large dividend increases and leverage - Cooper, Ian A.; Lambertides, Neophytos (My University, 2018)
This study documents the fact that large dividend increases are followed by a significant increase in leverage, consistent with management increasing the dividend to use up excess debt capacity. However, the leverage increase is not captured by a standard partial adjustment model of leverage. Nor does it reflect variables known to be related to dividend increases, such as firm maturity, investment, and risk. Instead, the dividend increase signals a complex change in the way firms adjust to their leverage target, but it does not signal a change in the target.
Keywords: Capital structure; Dividend policy; Dividend changes; Leverage